Construction of poly(ethylene glycol)-poly(L-lactic acid)-stearic acid aspirin-loaded reverse micelles and optimization of preparation process. Issue 1 (1st January 2020) - Min, Yunpeng; Zhang, Hang; Wang, Huiru; Song, Yimin
ABSTRACT: This work aims to study the construction of reverse aspirin-loaded micelles prepared from amphiphilic PEG-PLA-SA triblock copolymers and the optimization of the preparation process. Using polyethylene glycol (PEG) as the initiator, ring-opening polymerization of L-lactide (L-LA) was used to prepare PEG-PLA diblock copolymers. Final product PEG-PLA-SA triblock copolymers were prepared by the reaction of stearic acid (SA) and PEG-PLA catalyzed by 4-dimethylaminopyridine (DMAP) and N, N'-Dicyclohexylcarbodiimide (DCC). Fourier transform infrared spectrometer (FT-IR) was used to characterize the product structure. PEG-PLA-SA triblock copolymers self-assembled in toluene/ethanol/water system to form reverse micelles, which could encapsulate aspirin into a hydrophilic core. Dynamic light scattering (DLS) and transmission electron microscopy (TEM) were used to determine the size and morphology of reverse micelles. The results showed that the reverse micelles are spherical, with a particle size of less than 70 nm. Response surface analysis method was applied to optimize the preparation process of PEG-PLA-SA. In vitro drug release was achieved by embedding reverse aspirin-loaded micelles in the biocompatible membrane in phosphate buffer saline (PBS) at 37°C. In the first 8 h, the drug release rate of the triblock copolymers was slower than that of the diblock copolymers. After 8 h, the drug release rate of both tended to be flat. The stability of aspirin-loaded reverse micelles was studied through accelerated test. These results indicate that reverse micelle PEG-PLA-SA may be a promising carrier for hydrophilic drugs like aspirin.